469 New variant of reconstructive surgery for advanced vulvar cancer treatment. (4th December 2020) - Bubliieva, Olha; Kostiuchenko, Yevgeniy; Svintsitskiy, Valentyn; Motuziuk, Igor; Tsip, Nataly; Nespryadko, Sergiy; Samokhvalova, Alena; Sydorchuk, Oleg
Abstract : Introduction/Background: Surgical treatment of advanced vulvar malignant tumors usually requires immediate reconstruction. Large defects after pelvis, vagina, vulva, groin and perineum wide excision require closure with the usage of difficult reconstructive techniques. In this case the most suitable myocutaneous flap for reconstruction is rectus abdominis muscle flap, which provides the biggest volume of tissues to cover those large defects. Methodology: Woman 67 y.o. initially presented with the combined treatment of cervical cancer stage IIB. Within 5 month was diagnosed the lymphedema in the left lower extremity. Approximately 2 years she presented the vulvar tumor measured 15 × 10 cm. A biopsy was performed the lymphangiosarcoma. Results: In the National Cancer Institute of Ukraine we investigated a new variation of large defects reconstruction using rectus abdominis muscle flap. To collect a donor flap, we perform 3 arcuate incisions: one vertical by the medial line around the umbilicus, and two oblique incisions towards upper anterior iliac spine of one of the sides. In this way we use only one half of the abdomen, and in case of any complications with the flap or relapse of the disease we will have the second donor site for possible future re-operation. There is a narrow 'bridge' of tissues we leave between the excised donor and recipient sites. It is extremely important to preserve blood supply not only to the flap, but also to the 'bridge' to avoid complications. We perform a tunnel under the 'bridge' as small as possible to preserve all inferior epigastric vessels, but enough to transfer the flap and not to squeeze the pedicle. After the surgery we have a half-inverted Y-shaped scar on of the sides of the abdomen, an inverted triangular scar at the pelvis area, circumumbilical scar and a short vertical scar on the flap to imitate pudendal cleft with central structures of vulva (urethra and vaginal tube). Conclusion: We consider our variation of this type of surgery the most safe and efficient, with the opportunity of re-operation if needed. Advanced vulvar malignancies are quite rare, so we will keep working on development and enhancement of the technique to help these patients. Disclosures: Authors declare no disclosures.